1997
DOI: 10.1111/j.1365-2923.1997.tb00045.x
|View full text |Cite
|
Sign up to set email alerts
|

Cultural diversity in Australian medical education

Abstract: The present study sought to explore the relevance of cultural dimensions and cultural diversity among overseas and local medical students. The main comparison among the fourth year medical students studied was between Asian origin and Anglophone background students. The measures used included cultural variation, reasons for studying medicine, learning approaches and strategies, patient interaction confidence, and medical practices anxieties. Results indicated cultural differences between the two groups, and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 9 publications
3
33
0
Order By: Relevance
“…Research elsewhere has identified personal, social, cultural, and financial pressures that may particularly affect students from non-mainstream backgrounds and that may need to be addressed explicitly and proactively 18 19. Failure in clinical examinations may have a sex related or cultural basis because the current emphasis on patient centred, empathetic care may be more natural for women than for men20 and may present a considerable difficulty for students from more paternalistic cultures 21 22 23 24. Language barriers may be important because fluency in standard English may not be adequate for medical and colloquial needs 25 26 27…”
Section: Discussionmentioning
confidence: 99%
“…Research elsewhere has identified personal, social, cultural, and financial pressures that may particularly affect students from non-mainstream backgrounds and that may need to be addressed explicitly and proactively 18 19. Failure in clinical examinations may have a sex related or cultural basis because the current emphasis on patient centred, empathetic care may be more natural for women than for men20 and may present a considerable difficulty for students from more paternalistic cultures 21 22 23 24. Language barriers may be important because fluency in standard English may not be adequate for medical and colloquial needs 25 26 27…”
Section: Discussionmentioning
confidence: 99%
“…Although not within the scope of the current contribution, there is certainly sufficient information to warrant another discussion relating to the different behaviours associated with collectivist and individualist cultures in the context of learning in PBL (Hofstede, 1986;Tennant, 1997;Klimidis et al, 1997).…”
Section: Social Domainmentioning
confidence: 98%
“…Although research on how individual dispositions play out in different cultures is not conclusive, consistent findings on either the cultural or individual ends of these two concepts show their impact on a variety of outcomes relevant to acting and learning in healthcare workplaces. These range from mode of participation in the workplace, to approaches to dealing with errors, to the organization and public expenditure on healthcare (Klimidis et al 1997;Bell 2007;Gelfand et al 2011;Castilla 2004). …”
Section: Inside Versus Outside Anchorsmentioning
confidence: 99%